Removing redundancy for attribute implications in data with grades - Mora-Bonilla, Ángel; Rodríguez-Lorenzo, Estrella; Cordero-Ortega, Pablo; Enciso-García-Oliveros, Manuel (Cristina Alcalde, Humberto Bustince, Francisco Javier Fernández, 2016)
Reasoning with if-then rules –in particular, with those taking from of implications between conjunctions of attributes– is crucial in many disciplines ranging from theoretical computer science to applications. One of the most important problems regarding the rules is to remove redundancies in order to obtain equivalent implicational sets with lower size.
Keywords: Lógica Difusa; Implicaciones; Redundancia